STRATEGI MEINGKATKAN MINAT BELI ULANG APTEK TERHADAP PRODUK OBAT PT NOVELL PHARMACEUTICAL LABS MEDAN - Manuntun Pakpahan (UNIVERSITAS PEMBANGUNAN PANCA BUDI, 2016)
Sales performance is important to analyze the cause of the common goal of everycompany is to gain certain advantages, and it will be achieved if the sales activitiescan be carried out successfully as planned. Since 2010, decreases in the number ofpharmaceutical customers, both existing customers and new customers. Decreasingthe number of pharmacies turns is directly proportional to the frequency of repeatpurchases reduced, up to 1,487 times in 2014. It is an indication of a problem tobuy the pharmaceutical interests. The purpose of this study was to identify thefactors that influence buying interest again and find strategies to increase sales,especially in pharmacy customers. This research is a correlational study. Thepopulation in this study were 91 pharmacies still be customers of PT NovellPharmaceutical Sector Labs. Analysis of the data used is multiple regressionanalysis. Quality of service, competence of the sales and the price effect of 39.1%of the interest re buying, while 60.9% are influenced by other factors not examinedin this study. Competence factor sales people give the most dominant influence onthe purchasing pharmaceutical interests in PT Novell Pharmaceuticall Field Labs.